Acute Tubular Necrosis Associated with Autoimmune Hemolytic Anemia due to Acute Gastroenteritis - Mehmet Sezen; Abdülmecit Yıldız; Mahmut Yavuz; Kamil Dilek; Mustafa Güllülü; Ayşegül Oruç; Mehmet Fethullah Aydın; Alparslan Ersoy (Turkish Journal of Internal Medicine, 2021)
Abstract Autoimmune hemolytic anemia (AIHA) is a rare disease with a rate of 1-3 in 100,000 in adults. AIHA are defined as primary (idiopathic) or secondary depending on the presence or absence of accompanying disease. Secondary causes include drugs, immunodeficiencies, infections, other autoimmune diseases, or malignancies. Here, we report an 42-year-old female presented to us with diarrhea, nausea-vomiting, fever, chills and jaundice for two days. Hematological investigations revealed hemolytic anemia. Direct Coombs test was positive. The patient was diagnosed acute tubuler necrosis with autoimmune hemolytic anemia. Methylprednisolone 40 mg/day was started considering autoimmune hemolytic anemia. She was on hemodialysis at regular intervals. After 4 weeks, the patient was symptomatically improved with remission of acute tubuler necrosis and hemolytic anemia. In our case, the association of AIHA due to acute gastroenteritis and acute tubular insufficiency was considered suitable for the presentation because of its rare occurrence.